Ezekiel’s Vision Accounts as Interrelated Narratives A Redaction-Critical and Theological Study - Hiebel, Janina Maria 1979- (Berlin Bosten De Gruyter, 2015)
This study on the vision accounts in the book of Ezekielcombines redaction criticism with questions ofrhetorical and narrative criticism. It offers a united redaction history that reflects the growing interrelationship of the vision accounts over time. A second, more theological part follows the development of selected themes in the visions’ discourse and theology throughout the stages of redaction.
Perth, 2013, Western Australia, Murdoch Univ., Diss.-2014
In English
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, Redaction; Visions in the Bible; Visions in the Bible; RELIGION / Biblical Studies / Old Testament; Ezekiel; literary criticism; redaction criticism; visions; Hochschulschrift